2013
DOI: 10.1002/micr.22107
|View full text |Cite
|
Sign up to set email alerts
|

Anemia is not a predictor of free flap failure: A review of NSQIP data

Abstract: Background Thrombosis is a common cause of flap failure in microvascular tissue transfer, which questions the effects of anemia on this outcome. This article seeks to contribute a large, multi‐institutional data analysis to this debate. Methods Free tissue transfer patients were identified in the National Surgical Quality Improvement database through a specified Current Procedural Terminology algorithm. Bivariate analysis compared anemic and nonanemic groups with respect to flap failure and other outcomes. Mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
30
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 38 publications
3
30
0
Order By: Relevance
“…Our own data reviewing preoperative hematocrit and free flap failure showed no relationship between flap failure and anemia, but did demonstrate increased reoperation rates and surgical complications in the anemic cohort (p ¼ 0.022 and p ¼ 0.082, respectively). 24 In contrast, a study by Namdar et al found a significant association between saline infusion volumes and flap loss, as well as total infusion volume to body weight ratios and flap loss. 46 Again, they were limited by a sample size of 48, with only four flap losses.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Our own data reviewing preoperative hematocrit and free flap failure showed no relationship between flap failure and anemia, but did demonstrate increased reoperation rates and surgical complications in the anemic cohort (p ¼ 0.022 and p ¼ 0.082, respectively). 24 In contrast, a study by Namdar et al found a significant association between saline infusion volumes and flap loss, as well as total infusion volume to body weight ratios and flap loss. 46 Again, they were limited by a sample size of 48, with only four flap losses.…”
Section: Discussionmentioning
confidence: 86%
“…23 A recent study of 864 free flap patients did not find any relationship between preoperative hemoglobin level and flap-related complications. 24 Keywords ► transfusion ► free flap ► microsurgery ► NSQIP…”
mentioning
confidence: 99%
“…However, our study showed that hypertension (AOR, 0.36) and debates mellitus (AOR, 0.35) were associated with a lower rate of flap thrombosis with unknown etiology. Although, we did not evaluate the effect of anemia on flap thrombosis, Mlodinow et al showed that anemia is neither a predictor of free tissue transfer failure nor is it protective. Age, too, was a patient variable that did not affect the rate of thrombotic complications.…”
Section: Discussionmentioning
confidence: 90%
“…A literature review showed inconsistent results concerning the effect of preoperative anemia on postoperative flap failure. A recent study using the National Surgical Quality Improvement Program demonstrated that preoperative anemia did not predict flap failure after free flap reconstructive surgery . By contrast, another recent report showed that preoperative anemia was directly related to vascular thrombosis and free flap failure in microvascular reconstruction, and especially, patients with preoperative hematocrit level less than 30% had more chance of flap failure .…”
Section: Discussionmentioning
confidence: 97%